ANALISIS HASIL IMPLEMETASI KURIKULUM MERDEKA PADA MATA PELAJARAN IPAS DI KELAS IV SD NEGERI 1 JEKETRO - prasena arisyanto; Fine Reffiane; ifa farkhati (Indonesian Journal of Elementary School, 2023)
This research aims to describe: 1) to analyze the implementation of the independent curriculum in Class IV science and science learning at SD Negeri 1 Jeketro, 2) to analyze the constraints and obstacles in implementing the independent curriculum in Class IV science and science learning at SD Negeri 1 Jeketro, 3) to analyze efforts to overcome constraints and obstacles in implementing the independent curriculum in Class IV science and science learning at SD Negeri 1 Jeketro. This research is a qualitative research. The research was carried out at SD Negeri 1 Jeketro in June 2023. The subjects of this research were the Principal, Class IV Teachers, and Class IV Students. Data collection techniques were carried out using observation, interviews and documentation. Activities in qualitative data analysis using interactive models are data collection, data reduction, display, and conclusion drawing.The results of this research show that: 1) the implementation of the independent curriculum in science and science learning has been well realized, the planning carried out was by analyzing the CP, compiling the TP, and creating the ATP. The learning implementation has implemented differentiated learning tailored to students' needs and has prepared evaluations in the form of diagnostic assessments, formative and summative assessments, 2) there are obstacles and barriers such as less valid information, few reference sources, limited time in preparing teaching and assessment modules, 3) Efforts are made to overcome constraints and obstacles, namely by participating in seminars, webinars and workshops, increasing reference sources and utilizing guidebooks for preparing teaching modules provided by the government.